An updated portrait of monocyte-macrophages in classical Hodgkin lymphoma - Ferrarini, Isacco; Bernardelli, Andrea; Lovato, Ester; Schena, Alberto; Krampera, Mauro; Visco, Carlo (Frontiers in Oncology, 2023)
Classical Hodgkin lymphoma (cHL) is a unique neoplastic ecosystem characterized by a heterogeneous immune infiltrate surrounding the rare malignant Hodgkin Reed-Sternberg cells. Though less abundant than T-cells, tumor-infiltrating macrophages play a pivotal role in supporting HRS survival through cell-to-cell and paracrine interactions. Traditional immunohistochemistry based upon the M1-M2 dichotomy yielded controversial results about the composition, functional role and prognostic impact of macrophages in cHL. More recent studies exploiting single-cell technologies and image analyses have highlighted the heterogeneity and the peculiar spatial arrangement of the macrophagic infiltrate, with the most immunosuppressive subpopulations lying in close proximity of HRS cells and the most tumor-hostile subsets kept far away from the neoplastic niches. High-throughput analysis of peripheral blood mononuclear cells in cHL patients have also identified a novel, potentially cytotoxic, subpopulation predicting better response to PD-1 blockade. This review examines the phenotypic profile, spatial localization and clinical impact of tumor-infiltrating macrophages and circulating monocytes in cHL, providing an up-do-date portrait of these innate immune cells with possible translational applications.